Selecting the right bird model in experimental studies on endocrine disrupting chemicals - Jaspers, Veerle L. B. (Frontiers in Environmental Science, 2015)
Birds have been used as model species in ecotoxicological research for decades but have only recently been included in toxicity testing schemes. However, the avian fauna is very diverse. Given this diversity the ecology, behavior and reproduction should be considered when selecting the appropriate bird model in ecotoxicological studies. This article focusses on choosing the right bird model species for experimental studies with endocrine disrupting chemicals (EDCs). EDCs have been associated with adverse effects on the reproduction and development in birds and other wildlife. In addition, new EDCs continue to emerge and the concern for potential effects in humans and wildlife is calling for increased toxicity testing and hence appropriate model species. Common bird model species used in ecotoxicological studies investigating EDCs will be reviewed. In addition, considerations for selecting the right bird model, along with potential drawbacks and restrictions on the use of certain species will be discussed.